2012
DOI: 10.1111/j.1365-3148.2012.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of trauma transfusion pathways for blood component transfusion in the civilian population: a systematic review and meta‐analysis*

Abstract: This study was undertaken to determine if, amongst civilian trauma patients requiring massive transfusion (MT), the use of a formal trauma transfusion pathway (TTP), in comparison with transfusion without a TTP, is associated with a reduction in mortality, or changes in indices of coagulation, blood product utilisation and complications. A systematic review of three bibliographic databases, reference lists and conference proceedings was conducted. Studies were included if comparisons were made between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Several systematic reviews and meta-analyses have summarized the findings from observational studies associating reduced in-hospital mortality with the establishment of massive transfusion protocols in Level I trauma centers (7 studies) 11, 12 and with increased plasma and platelet:RBC ratios closer to 1:1 (16 studies). 1316 In addition, clinical practice guidelines regarding the use of plasma 17 and platelet 18 transfusion for massively hemorrhaging patients have been published recently.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have summarized the findings from observational studies associating reduced in-hospital mortality with the establishment of massive transfusion protocols in Level I trauma centers (7 studies) 11, 12 and with increased plasma and platelet:RBC ratios closer to 1:1 (16 studies). 1316 In addition, clinical practice guidelines regarding the use of plasma 17 and platelet 18 transfusion for massively hemorrhaging patients have been published recently.…”
Section: Introductionmentioning
confidence: 99%
“…Vogt et al, in 2012, have found that early activation of MT protocol in resuscitation has found to have a double benefit of improved patient outcome as well as limit the usage of blood components and hence decreasing the complications associated. 18 The SI has proved to be a robust marker of ongoing hemorrhage, the need for MTs and is easily available in almost every setting. Vandromme et al has found SI to be important clinical marker in a prehospital setting but will need further evaluation before incorporating into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a massive transfusion protocol (MTP) improves outcomes. It results in a significant reduction in mortality without increased use of blood components 26 . MTPs facilitate communication between clinical stakeholders and the transfusion laboratory.…”
Section: Patient Blood Managementmentioning
confidence: 99%